Gender differences in nonviolence disposition among university students - Ardian Renata Manuardi; Uman Suherman; Ilfiandra Ilfiandra; Yusi Riska Yustiana (Jurnal Konseling dan Pendidikan, 2026)
This study was conducted in response to the increasing concern over aggressive behaviors among university students, highlighting the importance of understanding factors associated with nonviolent tendencies. This study aimed to examine gender differences in nonviolence disposition among university students. A comparative quantitative research design with a cross-sectional approach was employed. The participants consisted of 430 undergraduate students from IKIP Siliwangi, Indonesia, including 83 male students and 347 female students, aged 17–21 years. Data were collected through an online survey using an adapted version of the Teenage Nonviolence Test (TNT). Data were analyzed using descriptive statistics and an independent samples t-test. The results indicated that the overall nonviolence disposition of students was at a moderate level across all dimensions, based on the scale used in this study. Descriptive findings showed that female students consistently obtained higher mean scores than male students in nearly all dimensions. Inferential analysis revealed a statistically significant gender difference in Physical Nonviolence, with female students demonstrating higher levels than male students. This finding indicates that gender is associated with differences in students’ tendencies to reject physical aggression and refrain from using physical force in conflict situations.